Removal of ammonium from aqueous solution by ion exchange on natural and modified chabazite - Leyva-Ramos, R.; Monsivais-Rocha, J.E.; Aragon-Piña, A.; Berber-Mendoza, M.S.; Guerrero-Coronado, R.M.; Alonso-Davila, P.; Mendoza-Barron, J. (Journal of Environmental Management, 2010)
The ammonium exchange capacity of a natural chabazite was studied in this work. The XRD analysis of the zeolite sample revealed that the main zeolitic phase was chabazite. The textural properties were determined by the N-BET method and the surface morphology and charge were examined using a scanning electron microscope and a zetameter, respectively. The ion exchange equilibrium data were obtained in a batch adsorber and the Langmuir isotherm fitted plausibly well the equilibrium data. The effects of the temperature and pH on the ammonium exchange capacity of chabazite were investigated and the capacity increased augmenting the temperature from 15 to 35 °C and pH from 3 to 6. The natural chabazite was modified by a hydrothermal treatment using NaCl and KCl solutions and it was found that the modification influenced the ammonium exchange capacity of the chabazite. The ammonium capacity of natural chabazite was compared with that of a natural clinoptilolite and it was concluded that the chabazite capacity was 1.43 times higher than that of clinoptilolite.